Regional differences in population aging in Europe viewed through prospective indicators - Šídlo, Luděk; Šprocha, Branislav; Klapková, Michaela (ERDKUNDE, 2019)
Demographic aging has been one of the most discussed aspects of population development in recent decades. Complex changes in reproductive behaviour and their impact on both age structure and future population development are often the source of concerns about the stability of socioeconomic systems (e.g. pension systems, healthcare and the labour market). Frequently reinforced by the development and use of standard demographic aging indicators and comparisons over time and space and/or between populations, this one-sided view is problematic given significant changes in population mortality and health. Population aging has moreover traditionally been analysed in relation to national and regional differences, with specificities frequently being overlooked. Using new methods for analysing demographic aging based on prospective age, which accounts for changes in life expectancy over time and therefore more accurately captures demographic aging, we attempt to identify the main spatial patterns of regional differentiation in aging in Europe (at the NUTS2 level). We also attempt to create a typology of Europe’s regions using the main aging indicators and thereby identify the areas most affected by demographic aging.